(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The paper attempts to examine the economic contribution of rural women in Manipur through their earnings from various activities in the non-farm sector. The paper shows that non-farm sector employment plays a significant role in supporting the livelihoods of rural families in the state of Manipur. The paper is based on a field survey in Irengbam village of Bishnupur district in Manipur.